Heterogeneous Patterns of Aged Organic Carbon Export Driven by Hydrologic Flow Paths, Soil Texture, Fire, and Thaw in Discontinuous Permafrost Headwaters. Issue 4 (30th March 2022) - Koch, Joshua C.; Bogard, Matthew J.; Butman, David E.; Finlay, Kerri; Ebel, Brian; James, Jason; Johnston, Sarah Ellen; Jorgenson, M. Torre; Pastick, Neal J.; Spencer, Robert G. M.; Striegl, Robert; Walvoord, Michelle; et al.
Abstract: Climate change is thawing and potentially mobilizing vast quantities of organic carbon (OC) previously stored for millennia in permafrost soils of northern circumpolar landscapes. Climate‐driven increases in fire and thermokarst may play a key role in OC mobilization by thawing permafrost and promoting transport of OC. Yet, the extent of OC mobilization and mechanisms controlling terrestrial‐aquatic transfer are unclear. We demonstrate that hydrologic transport of soil dissolved OC (DOC) from the active layer and thawing permafrost to headwater streams is extremely heterogeneous and regulated by the interactions of soils, seasonal thaw, fire, and thermokarst. Repeated sampling of streams in eight headwater catchments of interior Alaska showed that the mean age of DOC for each stream ranges widely from modern to ∼2, 000 years B.P. Together, an endmember mixing model and nonlinear, generalized additive models demonstrated that Δ 14 C‐DOC signature (and mean age) increased from spring to fall, and was proportional to hydrologic contributions from a solute‐rich water source, related to presumed deeper flow paths found predominantly in silty catchments. This relationship was correlated with and mediated by catchment properties. Mean DOC ages were older in catchments with >50% burned area, indicating that fire is also an important explanatory variable. These observations underscore the high heterogeneity in aged C export and difficulty of extrapolating estimates of permafrost‐derived DOC export from watersheds to larger scales. Our results provide the foundation for developing a conceptual model of permafrost DOC export necessary for advancing understanding and prediction of land‐water C exchange in changing boreal landscapes. Plain Language Summary: In high latitude environments, soils that have been frozen for millennia are thawing, releasing organic carbon (OC). Thawing and export of OC to downstream aquatic ecosystems is a potential biogeochemical feedback that may accelerate climate warming if large amounts of ancient OC are transformed and released to the atmosphere as greenhouse gases. The magnitude and timing of ancient OC thaw and mobilization are not well defined, so predicting these patterns at local to global scales is challenging. Using a suite of diverse headwater catchments in the discontinuous permafrost zone of Alaska, USA, we identify the main controls on the mobilization of ancient OC from thawing landscapes into adjacent streams. Our surveys show that ancient OC export depends on the complex interaction between fire history, soil type and thawing characteristics, and seasonal warming. We find that all of these factors play a role, resulting in highly heterogeneous release of ancient OC to headwater streams. Key Points: Aged dissolved organic carbon (DOC) in headwater streams in interior Alaska is heterogeneous across permafrost landscapes indicating the interplay of multiple drivers Aged DOC concentrations increase from spring to fall and are highest in catchments with >50% burned extent and dominated by silty uplands Aged DOC is proportional to stream solute loads, indicating that deeper flow paths deliver permafrost C to streams